Numerical modeling of geometric and aerodynamic characteristics hvyntokiltsevoho engine - Лемко, О.Л.; Силка, Н.В. (Proceedings of National Aviation University (archive), 2009)
The some results of ring-belt airscrew propulsion development for a power plant of “convertiplane”-type air vehicle are described in this paper. It is shown, that the ring-belt airscrew propulsion with six-blade saber-shape airscrew is the most reasonable version in view of providing the predefined thrust .end profile Clark-Y.